Pengaruh Gaya Hidup, FOMO, Media Sosial Tiktok terhadap Perilaku Konsumtif dalam Perspektif Ekonomi Syariah - Eliza Reani Futri; Supardi Mursalin; Debby Arisandi (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2026)
This study aims to determine the influence of lifestyle, FOMO, and TikTok social media on consumer behavior from a Sharia Economic Perspective. The type of research used is quantitative research. The population of this study is active students of UINFAS Bengkulu, involving a sample size of 890 students from the class of 2021 and 2022, with a sample of 91 respondents. Data analysis includes validity tests, reliability tests, classical assumption tests, and hypothesis tests through multiple linear regression, F tests, t tests, and coefficients of determination to see the relationship between research variables. The type of research used is quantitative research. The results of the study indicate that 1) there is an influence of lifestyle on consumer behavior, meaning that the higher a person's lifestyle, the tendency to behave in a consumer manner also increases; 2) there is an influence of FOMO on consumer behavior, meaning that the fear of being left behind makes individuals more likely to buy without consideration; 3) there is an influence of TikTok social media on consumer behavior, meaning that the content displayed can influence users' purchasing decisions; and 4) there is a simultaneous influence of lifestyle, FOMO, and TikTok social media on consumer behavior, meaning that the three variables together strengthen consumer tendencies in individuals.